Software and Systems Traceability - Huang, Jane; Gotel, Orlena; Zisman, Andrea (Springer London : Imprint: Springer, 2012)
Traceability supports numerous activities in the engineering of software systems.  For example, pre-requirements traceability is used to demonstrate that a product meets the stakeholders' stated requirements, or that it complies with a set of government regulations. Other forms of traceability are used to demonstrate the relationships between requirements and software artefacts such as design models, source code, and test cases. Over the last 20 years, in order to overcome the significant challenges in creating, maintaining and using traceability, the research community has been actively addressing traceability issues through the following: Exploring topics related to automating the traceability process Developing strategies for achieving cost-effective traceability Supporting the capture and evolution of traceability links Visualizing traceability and advancing its effectiveness for end users Developing traceability practices that apply across a wide range of domains   Divided into five sections, Traceability Strategy, Traceability Creation, Traceability Maintenance, Traceability Use and Traceability Challenges, Software and Systems Traceability provides a comprehensive reference for traceability theory, research and practice and presents an introduction to the concepts and theoretical foundations of traceability.